Ultrasonography-guided de Quervain Injection: Accuracy and Anatomic Considerations in a Cadaver Model. Issue 6 (June 2016) - Leversedge, Fraser J.; Cotterell, Ilvy H.; Nickel, Brian; Crosmer, Megan; Richard, Marc; Angermeier, Eric
Abstract : Introduction: Confirmation of pertinent anatomy and accurate needle placement for de Quervain injection may improve outcomes and limit complications. We evaluated the accuracy of the first extensor compartment in regard to the following: (1) anatomic assessment, (2) needle placement without imaging guidance, and (3) ultrasonography-guided injection with priority for the extensor pollicis brevis subcompartment. Methods: Anatomic assessment and ultrasonography-guided first extensor compartment injection was completed in 50 cadaver specimens. Initial needle placement was done without the guidance of ultrasonography; its final position was evaluated with ultrasonography. Then, using ultrasonography, 1 mL of India ink was injected into the extensor pollicis brevis compartment. Open evaluation confirmed pertinent anatomy and injection accuracy. Results: A subcompartment of the first extensor compartment was identified in 27 of 50 wrists; 18 of 27 compartments were complete and 9 of 27 were incomplete, with ultrasonographic evaluation having an accuracy rate of 94%. Accurate needle placement occurred in 26 of 50 wrists (52%) when ultrasonography was not used, but only 2 of 27 needles (7%) were located within the extensor pollicis brevis subcompartment. Ultrasonography-guided injection was 100% accurate (50 out of 50) and extensor pollicis brevis injection was 96% accurate (26 of 27) when two compartments were present. Minimal extravasation was identified in 6 of 50 wrists (12%). Discussion: Ultrasonography-guided de Quervain injection improves injection accuracy through the visualization of compartmental anatomy and needle placement and may improve clinical outcomes by minimizing complications associated with extra-compartmental injection.